Enhancing lithium leaching by mechanical activation - Setoudeh, Nader; Nosrati, Ataollah; Welham, Nicholas J (Mongolian Journal of Chemistry, 2018)
The lithium (Li) bearing minerals lepidolite and spodumene were mixed with different mass ratios of Na2SO4 and mechanically activated by milling in a planetary ball mill for 5 h. The milled samples were studied using thermogravimetry under an air atmosphere up to 950 ºC. Isothermal heating of the milled samples was undertaken in a furnace at temperatures of 700 ºC and 800 ºC for 1 h. Hot water leaching of the calcines indicated that increasing the calcination temperature had a significant effect on the dissolution of lithium. The leaching of lithium from lepidolite was notably higher than that from spodumene.